2016
DOI: 10.1021/acs.iecr.6b00871
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Sol–Gel Derived Bismuth Silicate Dielectric Ink for Flexible Electronics Applications

Abstract: An agile formulation for the development of a low dielectric constant ink of nanostructured bismuth silicate (nBSO), synthesized by sol-gel method, was demonstrated. The viscous screen printable ink was formulated by controlling the organic additives. The viscosity, as well as dynamic viscoelastic properties of the formulated ink, was suitably tuned, to yield ideal flow characteristics. Microstructure and surface roughness of the printed film were characterized, and the film shows a minimum surface roughness v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…As the amount of ller increases the viscosity tends to increase and vice versa. 21,22 In other words, as more and more CNT is added, the ink becomes more concentrated and hence improves the viscosity. When the dispersant increases, it tends to disperse the CNT more uniformly, weakening the impact of agglomeration and thus decreasing the viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…As the amount of ller increases the viscosity tends to increase and vice versa. 21,22 In other words, as more and more CNT is added, the ink becomes more concentrated and hence improves the viscosity. When the dispersant increases, it tends to disperse the CNT more uniformly, weakening the impact of agglomeration and thus decreasing the viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the current density increases in an exponential manner after a particular applied field, which is common in the case of many dielectrics. 56,57 Moreover, it is clear that the material possesses a comparatively lower leakage current density. This is to be understood, considering the lamellar arrangement of the exfoliated BN nanosheets between two high-voltage electrodes, wherein electrons have to travel a longer path to drift through the edges of the nanosheets in comparison with the nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…These values were in good agreement with the earlier reports on screen-printable inks. 34,36 Profile symmetry information was obtained from the skewness value of the film. Because bumps and valleys are predominant in the developed film, the expected skewness moment is negative.…”
Section: Resultsmentioning
confidence: 99%